2020
DOI: 10.3390/cancers12061421
|View full text |Cite
|
Sign up to set email alerts
|

Galectins and Ovarian Cancer

Abstract: Ovarian cancer is known for its aggressive pathological features, including the capacity to undergo epithelial to mesenchymal transition, promoting angiogenesis, metastatic potential, chemoresistance, inhibiting apoptosis, immunosuppression and promoting stem-like features. Galectins, a family of glycan-binding proteins defined by a conserved carbohydrate recognition domain, can modulate many of these processes, enabling them to contribute to the pathology of ovarian cancer. Our goal herein was to review speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 168 publications
(267 reference statements)
1
26
0
3
Order By: Relevance
“…Overall, the literature seems to suggest that galectin overexpression is a poor prognostic factor that enhances the development, progression, and metastasis of several cancer types 8 . In addition, monitoring galectin‐mediated pathways could be of great importance in improving the quality of care 28 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, the literature seems to suggest that galectin overexpression is a poor prognostic factor that enhances the development, progression, and metastasis of several cancer types 8 . In addition, monitoring galectin‐mediated pathways could be of great importance in improving the quality of care 28 …”
Section: Discussionmentioning
confidence: 99%
“…Data on the interaction of galectin-9 and TIM-3 are contradictory. Galectin-9 is involved in oncogenesis, cell transformation, cell cycle regulation, cell adhesion, and angiogenesis [ 13 ]. It was shown that galectin-9 binding to the TIM-3 molecule on the surface of T-helpers terminates the T-cell antitumor immune response [ 14 ].…”
Section: Immune Checkpoint Receptorsmentioning
confidence: 99%
“…Hanahan and Weinberg defined hallmarks of most cancers which describe the biological capabilities essential for carcinogenesis [ 31 ]. There are a number of papers published regarding the subject of cancer (development) and the roles of (targeting) galectins, and even galectin-7 in particular [ 13 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Nevertheless, our goal for this section is to provide the reader with a brief overview of the presence and roles of galectin-7 in most cancers/cancer types by covering mostly recent publications.…”
Section: Galectin-7 a Convergence Of Pathology With Physiologymentioning
confidence: 99%